Correlation of forced oscillation technique in preschool children with cystic fibrosis with pulmonary inflammation. Issue 2 (28th January 2005) - Brennan, S; Hall, G L; Horak, F; Moeller, A; Pitrez, P M C; Franzmann, A; Turner, S; de Klerk, N; Franklin, P; Winfield, K R; Balding, E; Stick, S M; et al.
Abstract : Background: Lung disease in cystic fibrosis (CF) is established in early childhood with recurrent bacterial infections and inflammation. Using spirometry, the effect of this early lung damage cannot be measured until a child is 6 years of age when some irreversible lung damage may already have occurred. Techniques for measurement of lung function in infants and young children include raised volume rapid thoracic compression (RVRTC) and low frequency forced oscillation (LFFOT). The aim of this study was to investigate the role of inflammation and infection on a population of infants and young children with CF and to determine whether lung function in this population (measured by LFFOT) is affected by early lung disease. Methods: Lung function was measured by LFFOT in 24 children undergoing bronchoalveolar lavage (BAL) on 27 occasions as part of an annual programme while still under general anaesthesia. Following lung function testing, three aliquots of saline were instilled into the right middle or lower lobe. The first aliquot retrieved was processed for the detection of microbes, and the remaining aliquots were pooled to assess inflammatory markers (cytology, IL-8, NE, LTB4 ). Results: Inflammation (percentage and number of neutrophils) was significantly higher in children with infections (p<0.001, p = 0.04, respectively), but not in those with symptoms. Several markers of inflammation significantly correlated with LFFOT parameters (R, G, and η). Conclusion: Infections and inflammation are established before symptoms are apparent. Inflammation is correlated with measures of parenchymal changes in lung function measured by LFFOT.